MRI and PET Image Fusion Using Fuzzy Logic and Image Local Features - Umer Javed; Muhammad Mohsin Riaz; Abdul Ghafoor; Syed Sohaib Ali; Tanveer Ahmed Cheema (The Scientific World Journal)
An image fusion technique for magnetic resonance imaging (MRI) and positron emission tomography (PET) using local features and fuzzy logic is presented. The aim of proposed technique is to maximally combine useful information present in MRI and PET images. Image local features are extracted and combined with fuzzy logic to compute weights for each pixel. Simulation results show that the proposed scheme produces significantly better results compared to state-of-art schemes.